Historia Global: Perspectivas y Tensiones - Aranha, Patricia (Historamericana, 2022)
The central idea that inspires this work is the study of interconnected history, as an alternative to history by area cultural or comparative. Therefore, the proposed approach is directly inscribed in what is known as global history.